A new & correct map of the whole world : shewing ye situation of its principal parts. Viz the oceans, kingdoms, rivers, capes, ports, mountains, woods, trade-winds, monsoons, variation of ye compass, climats, &c. With the most remarkable tracks of the bold attempts which have been made to find out the North East & North West Passages. - Moll, Herman, d. 1732 (J. Bowles, 1719)
Map shows trade winds and monsoons with Australia as New Holland coast joined to N. Guinea and the east coast un-mapped; explorers routes in the North Atlantic, political boundaries, and ocean currents. Includes explanation, scale of English leagues, and text notes. Insets: "This chart is to shew ye degrees of the variation of ye compass as they were observed in ye year of 1700 in ye Atlantick and Indian Ocean" and "The North Pole." Relief shown pictorially. Scale [ca. 1:34,000,000].